The Mangyans of Mindoro - Romualdez, Philip (New Jersey Prentice-Hall International,Inc., 1978)
A teenager's narrative and photographs depict the life of a primitive tribe living in the mountains of Mindoro.
Fi-16480g donated by Prof. Mamoru Tsuda.
Keywords: Mangyan (Philippine people) -- Juvenile literature; Children's writings